Descriptions of four new species, redescription of Paraliparis membranaceus, and additional data on species of the fish family Liparidae (Pisces, Scorpaeniformes) from the west coast of South America and the Indian Ocean - Stein, David L. (Zootaxa, 2005)
Liparids are a cottoid family of more than 350 species distributed worldwide in polar, temperate and deep tropical waters. About 20 species (in six genera) are known from the west coast of South America south of Panama to Tierra del Fuego, and four (in two genera) from the Indian Ocean. This paper describes an additional four species from existing collections: three from Peruvian and Chilean waters (Paraliparis carlbondi new species, Paraliparis skeliphrus new species, Notoliparis antonbruuni new species), and one from the Indian Ocean (Psednos carolinae new species). Paraliparis membranaceus Günther is redescribed, a range extension and additional descriptive information is reported for Paraliparis merodontus Stein, additional descriptive information is provided for Careproctus pallidus (Vaillant) and Psednos steini Chernova, the known range of Careproctus longifilis Garman is extended to Peru from the Gulf of Panama, and a species of Psednos similar to Psednos dentatus Chernova and Stein is described, but not named.